The case for FAT10 as a novel target in fatty liver diseases - Wimalarathne, Madushika M.; Wilkerson-Vidal, Quiana C.; Hunt, Emily C.; Love-Rutledge, Sharifa T. (Frontiers in Pharmacology, 2022)
Human leukocyte antigen F locus adjacent transcript 10 (FAT10) is a ubiquitin-like protein that targets proteins for degradation. TNFα and IFNγ upregulate FAT10, which increases susceptibility to inflammation-driven diseases like nonalcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH), and hepatocellular carcinoma (HCC). It is well established that inflammation contributes to fatty liver disease, but how inflammation contributes to upregulation and what genes are involved is still poorly understood. New evidence shows that FAT10 plays a role in mitophagy, autophagy, insulin signaling, insulin resistance, and inflammation which may be directly associated with fatty liver disease development. This review will summarize the current literature regarding FAT10 role in developing liver diseases and potential therapeutic targets for nonalcoholic/alcoholic fatty liver disease and hepatocellular carcinoma.